THE ROLE OF TRANSLATION IN PROMOTING THE UZBEK LANGUAGE AND CULTURE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In the era of globalization, presenting national languages and cultures to the global community requires accurate translation. Translating literary, scientific, and cultural works into and out of Uzbek is an important part of Uzbekistan's efforts to promote its national identity and linguistic legacy. This paper investigates how translation fosters intercultural communication, broadens the Uzbek language's global reach, and serves as a bridge between cultures. Additionally, it talks about the difficulties translators encounter when translating Uzbek cultural ideas into other languages and provides suggestions for enhancing translation quality and visibility in international settings.